2012
DOI: 10.3390/molecules17078037
|View full text |Cite
|
Sign up to set email alerts
|

6-Shogaol-Rich Extract from Ginger Up-Regulates the Antioxidant Defense Systems in Cells and Mice

Abstract: The rhizome of ginger (Zingiber officinale Roscoe) is known to have several bioactive compounds including gingerols and shogaols which possess beneficial health properties such as anti-inflammatory and chemopreventive effects. Based on recent observations that 6-shogaol may have more potent bioactivity than 6-gingerol, we obtained a 6-shogaol-rich extract from ginger and examined its effects on the nuclear factor E2-related factor2 (Nrf2)/antioxidant response element (ARE) pathway in vitro and in vivo. 6-Shoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 56 publications
6
65
0
1
Order By: Relevance
“…For instance, flavonoids and sulfurcontaining compounds (diallyl sulfide, trisulfide and allylcysteine), the two main classes of antioxidant components have been reported in garlic. 21 Moreover, ginger has been found to contain zingerone, gingerdiol, zingibranes, gingerols and shegaols (all polyphenols), which also posses antioxidant activity. 22 Thus, the protective effect exerted by the spices mixture may in part be attributed to the biological active ingredients present in this mixture.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, flavonoids and sulfurcontaining compounds (diallyl sulfide, trisulfide and allylcysteine), the two main classes of antioxidant components have been reported in garlic. 21 Moreover, ginger has been found to contain zingerone, gingerdiol, zingibranes, gingerols and shegaols (all polyphenols), which also posses antioxidant activity. 22 Thus, the protective effect exerted by the spices mixture may in part be attributed to the biological active ingredients present in this mixture.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently reported that [6]shogaol exhibits potent antioxidant and anti-inflammatory activities, its enone moiety being essential for these activities. 22,23 Interestingly, [6]-shogaol enhances antioxidant defense mechanisms both in cell cultures and in mice 24 and counteracts the hydrogen peroxide-induced increase of reactive oxygen species (ROS) in HT22 cells, an in vitro model of hippocampal cholinergic neurons. 25 Herein, we describe the design, synthesis, and pharmacological evaluation of a short series of multitarget antiAlzheimer hybrid compounds that combine a unit of the highly potent AChE inhibitor huprine Y (2, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Bak et al 27 have studied the effect of 6-shogaol enriched ginger extract on the antioxidant defense mechanism in mouse models. Their study showed that 6-shogaol rich extract enhanced the antioxidant defense mechanism through induction of the nuclear factor E2-related factor 2 (Nrf2) in vitro and in vivo.…”
Section: Antioxidant Activitymentioning
confidence: 99%